Deep Space Insights: Machine Learning Revolutionizing Astrophysical Discoveries - Dutta Samya; Paul Prithwineel (EPJ Web of Conferences)
This paper examines the transformative role of machine learning (ML) in astrophysics. With the exponential growth of astronomical data, traditional methods are often insufficient for effective data management and analysis. This paper provides a comprehensive overview of various machine learning algorithms applied across different subfields of astrophysics, elucidating their applications, advantages, and the challenges they address. Convolutional Neural Networks are essential for visual data analysis, helping in galaxy classification and exoplanet transit detection. SVMs and Random Forests improve the accuracy of classification and handle noisy data, especially in exoplanet detection and gravitational wave analysis. Autoencoders and RNNs are used for anomaly detection and time-series analysis, respectively, while GANs enhance the resolution of cosmological simulations. These significant contributions have come through with machine learning concerning galaxy classification, gravitational wave detection, exoplanet detection, and analysis upscaling of N-body simulations and dark matter detection and cosmic expansion. It integrates Machine Learning as a highly impressive advancement for making scalable, efficient, and accurate tools for astronomical data which face increasing complexity and volume. This integration enhances our knowledge regarding the universe while opening up new avenues for discovery. It allows scientists to grasp the cosmos at unprecedented levels. The paper concludes with a preview of future potential in ML for astrophysics, particularly discussing ongoing research and novel algorithms designed specifically to target challenges of astronomical data.